Case Report: Very Late, Atypical Extra-Medullary Relapse in a Patient With Acute Promyelocytic Leukemia (APL) Rescued With a Transplant-Free Approach - Molica, Matteo; Mazzone, Carla; Ottone, Tiziana; Niscola, Pasquale; Abruzzese, Elisabetta; Fratoni, Stefano; Voso, Maria Teresa; de Fabritiis, Paolo (Frontiers in Oncology, 2021)
Relapses of acute promyelocytic leukemia (APL) beyond 7 years from the first molecular remission are exceptional, and it is unclear whether these relapses represent a new, therapy-related leukemia rather than a delayed relapse of the original leukemic clone. The increase extra-medullary relapses (ER) in the era of all-trans retinoic acid (ATRA) therapy suggests a potential correlation between ATRA therapy and ER, and several potential explanations have been proposed. The gold standard post-remission approach, particularly for patients in late relapse, has not yet been established. The benefit of a transplant approach has been questioned in this setting because continuing ATRA- arsenic trioxide (ATO) might be curative. Here we report on the case of an APL patient who relapsed 9 years after achieving her first molecular complete remission (mCR) and who showed an atypical isolated localization at nodal sites including the into- and peri-parotid gland. Genomic PML/RARa breakpoint analysis detected the same bcr3 PML/RARa hybrid gene in DNA purified from bone marrow and lymph nodes, suggesting that the relapse was due to reemergence of the initial clone. This case shows that APL, treated with ATRA and cytotoxic drugs, may still emerge in extra-medullary sites even after a very prolonged mCR and can be salvaged with an ATO-based protocol not including a transplant approach.